(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Triage serves as the cornerstone of emergency department (ED) management, guiding prioritization of care based on clinical urgency. In high-volume EDs, the accuracy of triage decisions is crucial to ensure timely intervention and optimal resource utilization. Objective: This study aimed to assess the accuracy of triage classifications and evaluate their association with key patient outcomes. Methods: This cross-sectional analytical study was conducted at Tertiary Care Hospital from Nov 2024 to April 2025. A total of 155 patients were included in the study. The sample size was determined based on expected proportions of triage accuracy and clinical outcome distributions from existing literature, with a confidence level of 95% and an acceptable margin of error. Triage level at the time of presentation was documented using the institutional triage system in place (e.g., Emergency Severity Index or equivalent). A team of emergency medicine consultants independently reviewed each case retrospectively within the first hour of presentation, using presenting complaints, vital signs, and early clinical findings to assign a reference triage category. Results: Out of the 155 patients, 103 (66.5%) were accurately triaged, while 28 (18.1%) were undertriaged and 24 (15.4%) were overtriaged. Undertriaged patients showed significantly higher rates of ICU transfer (42.9%, p < 0.001) and mortality (17.9%, p = 0.020) compared to accurately triaged individuals. Overtriaged patients experienced the longest median ED stay (8.3 hours, p = 0.002). Hospital admission was significantly associated with triage accuracy (p = 0.008), with undertriaged patients more frequently requiring inpatient care. Conclusion: Triage inaccuracy, particularly undertriage, is associated with poorer clinical outcomes including higher ICU admission and mortality rates. These findings underscore the importance of ongoing training, regular audit, and decision-support tools to enhance triage accuracy in high-volume emergency departments.